Capsaicin attenuates the effect of inflammatory cytokines in a HaCaT cell model for basal keratinocytes - Cervantes Recalde, Maria Fernanda; Schmidt, Jana; Girardi, Cristina; Massironi, Marco; Rechl, Markus Leo; Hans, Joachim; Stuhlmann, Dominik; Somoza, Veronika; Lieder, Barbara (Frontiers in Pharmacology, 2024)
The resolution of the skin's inflammatory response is only possible if its barrier function is restored. TRPV1 channel activation plays an important role during inflammation but the effect of this activation on the skin barrier under inflammatory conditions has not been clarified. We hypothesize that it could potentially aid the keratinocyte barrier by reducing inflammatory cytokine release and promoting tight junction development. To explore the role of TRPV1 activation in inflammation, we designed and optimized an in vitro model of keratinocytes with basal epidermal layer characteristics using HaCaT cells and TNFα to induce inflammation. TNFα increased the gene expression of tight junction protein claudin 1 (CLDN1) by at least 2.60 ± 0.16-fold, in a concentration-dependent manner, over a 48 hour period. The administration of a capsaicin pre-treatment reduced the CLDN1 expression to 1.51 ± 0.16-fold during the first 6 hours after TNFα induction, whereas IL-8 cytokine release was reduced 0.64 ± 0.17-fold. After 48 hours, CLDN1 protein levels increased by a factor of 6.57 ± 1.39 compared to cells only treated with TNFα. These results suggest that activation of TRPV1 by capsaicin can potentiate the increase in CLDN1 expression and CLDN1 protein synthesis induced by TNFα in cultured keratinocytes, while reducing the release of IL-8.